Gated Silica Mesoporous Materials in Sensing Applications - Sancenón, Félix (ChemistryOpen, 2015)
Silica mesoporous supports (SMSs) have a large specific surface area and volume and are particularly exciting vehicles for delivery applications. Such container-like structures can be loaded with numerous different chemical substances, such as drugs and reporters. Gated systems also contain addressable functions at openings of voids, and cargo delivery can be controlled on-command using chemical, biochemical or physical stimuli. Many of these gated SMSs have been applied for drug delivery. However, fewer examples of their use in sensing protocols have been reported. The approach of applying SMSs in sensing uses another concept—that of loading pores with a reporter and designing a capping mechanism that is selectively opened in the presence of a target analyte, which results in the delivery of the reporter. According to this concept, we provide herein a complete compilation of published examples of probes based on the use of capped SMSs for sensing. Examples for the detection of anions, cations, small molecules and biomolecules are provided. The diverse range of gated silica mesoporous materials presented here highlights their usefulness in recognition protocols.